Pre-post school educational intervention assessment on HPV vaccination attitudes and willingness. (30th September 2020) - Costantino, C; Restivo, V; Trucchi, C; Vella, C; Sannasardo, C E; Caracci, F; Scarpitta, F; Icardi, G; Casuccio, A; Vitale, F
Abstract: Background: In Italy, vaccination coverage against human Papilloma Virus (HPV) showed a decreasing trend during last years. Different reasons could lead to a decrease in HPV vaccination confidence, such as not taking part to school seminars on HPV infection and vaccination. A pre-post intervention study was conducted in order to assess the improvement of knowledge, attitudes and behavior on HPV-related diseases and willingness on HPV vaccination among secondary school students. Methods: Two anonymous pre-post intervention questionnaires made up of 25 and 8 items, respectively, were administered to a representative sample of students attending secondary schools of Palermo, Italy. Between the two questionnaire administration, an educational intervention on HPV-related diseases and HPV vaccination, conducted by Public Health medical residents at the University of Palermo, was carried out. Results: During 2017/2018 and 2018/2019 school years, a sample of 1702 students, attending 18 first-grade secondary schools of the Province of Palermo, was enrolled. Evaluating a 10-scale likert question on the willingness of the children regarding vaccination against HPV, a significant increase of the average score from 8.50 (SD ± 1.79) to 9.01 (SD ± 1.50) (p value <0.001) was observed after intervention. At the multivariate analysis, male students (adjOR 1.76; 95% CI 1.28-2.42) and students attending schools in areas with a high deprivation index (adjOR 1.25; CI 95 % 1.01-1.55), showed a lower increase in HPV vaccination willingness after the educational intervention. In addition, 188 children from 5 schools of more deprived areas, not yet immunized, were vaccinated against HPV. Conclusions: Standardized educational interventions in the school environment could increase confidence towards HPV and other vaccinations among students. Furthermore, vaccination offer at schools could represent a fundamental strategy to increase vaccination coverage, especially in more deprived areas. Key messages: The research confirms the effectiveness of school educational interventions in increasing HPV vaccination confidence. Vaccination offer at schools could represent a fundamental strategy to increase vaccination coverage especially in more deprived areas.